A history of German literature. - Rose, Ernst, 1899- 4 0 16; 5 ([New York] : New York University Press, 1960)
Although partly based on a book the author wrote twenty-four years before, the chapters on Goethe, on Holderin, and Heine have been rewritten, while the chapters on Rilke, Thomas Mann, and Kafka contain new passages. There is much rephrasing and revision. Also the general emphasis is changed, in that general cultural history has been used as a background rather than a basis.
Partly based on the author's Geschichte der deutschen Literatur auf kulturgeschichtlicher Grundlage.
Keywords: 2 -- 0; 6; Translations into English.;History and criticism.;History and criticism. -- German literature;German literature;German literature; 20; 2